Transcriptional Regulation of Mononuclear Phagocyte Development - Tussiwand, Roxane; Gautier, Emmanuel L. (Frontiers in Immunology, 2015)
Introduction The mononuclear-phagocyte system (MPS), which comprises dendritic cells (DCs), macrophages and monocytes, is a heterogeneous group of myeloid cells. The complexity of the MPS is equally reflected by the plasticity in function and phenotype that characterizes each subset depending on their location and activation state. Specialized subsets of Mononuclear Phagocytes (MP) reside in defined anatomical locations, are critical for the homeostatic maintenance of tissues, and provide the link between innate and adaptive immune responses during infections. The ability of MP to maintain or to induce the correct tolerogenic or inflammatory milieu also resides in their complex subset specialization. Such subset heterogeneity is obtained through lineage diversification and specification, which is controlled by defined transcriptional networks and programs. Understanding the MP biology means to define their transcriptional signature, which is required during lineage commitment, and which characterizes each subset’s features. This review will focus on the transcriptional regulation of the MPS; in particular what determines lineage commitment and functional identity; we will emphasizes recent advances in the field of single cell analysis and highlight unresolved questions in the field.